Resource management : a multiple case study of resource management in Swedish equine boarding businesses - Andersson, Julia; Gahne, Karolina; Gevert, David (SLU/Dept. of Economics, 2018)
The resource management in companies defines the competitive advantage and the profile of the products or services. With a better understanding of resource management, the companies may increase their success. A sector that is expanding is the equine sector in Sweden. The equine businesses have received increased attention both from the society and from researchers. However, literature regarding how these equine boarding businesses are managed is rare.